China's Economic Slowdown and International Inflation Dynamics - Leonard Salzmann (ZBW – Leibniz Information Centre for Economics, 2020)
I examine the impact of the Chinese economic slowdown that started after the Great Recession on global inflation dynamics. To this end, I fit a high-dimensional data set comprising macroeconomic indicators of 41 countries to a structural factor-augmented vector autoregressive model. My main findings are: (i) Business cycle shocks and especially demand shocks in China significantly spill over to inflation rates in the US, Europe, Asia, and Oceania and are transmitted by global oil, commodity, and steel prices. (ii) The decline in Chinese growth rates can be attributed to a combination of negative aggregate demand and supply shocks. (iii) Historical decompositions indicate that after 2014, these shocks lowered PPI inflation rates outside of China by up to 0.3 percentage points per quarter, resulting in a cumulative effect on the PPI of six percent. Hence, they markedly contributed to the decline in global inflation rates and hampered the recent upward trend. (iv) The Chinese influence is also reflected in interest rates outside of China by a reduction of yields at the current edge.
Keywords: E31; E32; E43; 330; China's Economic Slowdown; Global inflation; Spillovers; FAVAR